Autocad LT 98 basics through advanced - Madsen, David A. (Prentice Hall, 2000)
For any design drafting program such as mechanical, architectural and electrical drafting, and graphic design programs where AutoCAD LT 98 is used. This text/workbook takes students through the systematic use of AutoCAD LT 98-with emphasis on the proper use of drafting standards in several key disciplines.